Tanggung Jawab Sosial Penyelenggaraan pendidikan Yang bercirikan Keadilan Pada Masyarakat - Farid Th. Musa (JURNAL LEGALITAS, 2009)
Reolity happened now shows condition of opportunity to obtain education, including obliged to learn that there are still blocked by compulsion to pay various payment. on the contrary, too much letting frie sweet promises to the management of educatian with a real guarantee bewitchs. But on the contrary the promise is very difficult to bi realized- Hence doesn\'t surprise everyrwhere many demands for government to hold responsible to the promise. social responsibility is striving to gite again to public what which have been ontaining. Thereby will be created a partnership which more wellbalanced and profits, because pubtic which has increasiagly smart with existence of education. Kata Kunci: Tanggung Jawab Sosial, pendidikan, Keadilan, Masyarakat